2021
DOI: 10.1007/s43673-021-00012-5
|View full text |Cite
|
Sign up to set email alerts
|

Plasma bioscience and its application to medicine

Abstract: Nonthermal atmospheric pressure biocompatible plasma (NBP), alternatively called bio-cold plasma, is a partially ionized gas that consists of charged particles, neutral atoms and molecules, photons, an electric field, and heat. Recently, nonthermal plasma-based technology has been applied to bioscience, medicine, agriculture, food processing, and safety. Various plasma device configurations and electrode layouts has fast-tracked plasma applications in the treatment of biological and material surfaces. The NBP … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 471 publications
1
24
0
Order By: Relevance
“…CAP is a possible treatment to reduce the presence of infecting SARS-CoV-2 virions in the air and surface of environmental materials. CAP has been proven to be safe and effective in damaging capsid and nucleic acids thanks to the content of RONS generated during treatment [13] and inactivating SARS-CoV-2 on surfaces. [30] In this study, the effect of CAP on aerosolized SARS-CoV-2 viral particles is shown asefficient in inactivating the virus, even ifa low power (less than 9 W) was used to generate CAP.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…CAP is a possible treatment to reduce the presence of infecting SARS-CoV-2 virions in the air and surface of environmental materials. CAP has been proven to be safe and effective in damaging capsid and nucleic acids thanks to the content of RONS generated during treatment [13] and inactivating SARS-CoV-2 on surfaces. [30] In this study, the effect of CAP on aerosolized SARS-CoV-2 viral particles is shown asefficient in inactivating the virus, even ifa low power (less than 9 W) was used to generate CAP.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, CAP, an ionized gas able to produce a blend of bioactive components (e.g., reactive oxygen and nitrogen species [RONS], electric field, UV ray), can inactivate the aerosolized virus through various oxidative processes, damaging nucleic acid, and proteins and lipids, causing aggregation of viruses. [13,14] Moreover, CAP can also act as a particle filter, thanks to the effect of the associated electric field in imparting charge-driven filtration due to the induction of negative charging of particles. [15] For this reason, several studies have focused on the use of CAP for the decontamination of air from potential pathogens, for example, viruses.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the need to search for prospects for solutions in applied biomedical applications of plasma-chemically activated water was noted. Promising for further research is not only the establishment of the mechanisms and stability of the properties of such water after treatment, but also its safety as a food ingredient [14,23].…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…These drawbacks are driving research for a novel, highly e cient sterilization process. Among microbial inactivation strategies, non-thermal atmospheric pressure plasma has received increasing attention in biology, medicine [12][13][14] and the agricultural and food industries [15][16][17] .…”
Section: Introductionmentioning
confidence: 99%